Integration In The Process Of Knowledge As A General Scientific Concept - A.Sh.Usmonov (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
The article discusses various approaches to the notion of integration, defining integration as scientific knowledge, expressed in the formation of scientific concepts. It is emphasized that since the first mention until today the concept of integration in the pedagogical process developed rapidly, taking on various forms and content